Reframing Women’s Rights Activism in Contemporary Russia and Vladimir Putin’s Regime - Sagung Agung Sri Utari (CV. Era Digital Nusantara, 2024)
In 2012, Pussy Riots movement came to the surface of Putin’s authoritarian regime. A long with its colorful balaclavas and provocative sudden performance song ‘Mother of God Drive Putin Away’ has successfully challenged the feminist political engagement in Putin’s regime along with their potential impact in improving human rights practice in Russia. This case shows a symbiotic relationship between the feminist agenda and the opposition movement where they could strengthen each other while feminism is the foundation for addressing gender issues. The paper will be analyzed by scrutinizing the actors of the Pussy Riot movement along with the promotion of gender equality as their main agenda. Then, it will be continued by analyzing the link of the Pussy Riot case with human rights and gender politics in the current political process of Russia and Putin’s regime. The two ways the connection between the feminist agenda and the way of opposition movement posed by Pussy Riot will also be drawn. Ultimately, we will see how the case could contribute to gender and human rights advocacy, particularly women’s rights, improvement in Russia. Relying upon the feminist movement, it can be concluded that the feminist agenda of gender equality can expand women’s role in Russia and advance Human Rights advocacy in Putin’s regime. Keywords:, Gender, Pussy Riot, Russia, Women’s Right